Chenopodiaceae endémicas del Perú - León, Blanca (2006)
The Chenopodiaceae is represented in Peru by four genera and 20 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all of them herbs and shrubs. Here we recognize one endemic species in Atriplex. This endemic species grows in the Tropical Costal Desert, Subtropical Costal Desert and Desert Shrubland regions, from sea level to 1150 m elevation. This endemic species is not found within Peru’s protected area system.